The diagnosis and management of food allergies. Position paper of the Food Allergy Section the Polish Society of Allergology - Bartuzi, Zbigniew; Kaczmarski, Maciej; Czerwionka-Szaflarska, Mieczysława; Małaczyńska, Teresa; Krogulska, Aneta (Advances in Dermatology and Allergology/Postępy Dermatologii i Alergologii, 2017)
The paper concerns the current position of the Polish Society of Allergology Food Allergy Section on the diagnosis and management of food allergies. The aim of this position is to provide evidence-based recommendations on the diagnosis and management of patients with allergic hypersensitivity to foods. This position statement includes a systematic review of studies in three areas, namely, the epidemiology, diagnosis and management of food allergies. While taking into account the specific Polish setting, in this publication we also used the current European Academy of Allergy and Clinical Immunology (EAACI) position paper and other current position statements, including those of the United States National Institute of Allergy and Infectious Diseases (NIAID).